2016
DOI: 10.1002/jbm.a.35808
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage responses to 316L stainless steel and cobalt chromium alloys with different surface topographies

Abstract: The surface topography of a biomaterial plays a vital role in determining macrophage interactions and influencing immune response. In this study, we investigated the effect of smooth and microrough topographies of commonly used metallic biomaterials such as 316 L stainless steel (SS) and cobalt-chromium (CoCr) alloys on macrophage interactions. The macrophage adhesion was greater on CoCr compared to SS, irrespective of their topographies. The macrophage activation and the secretion of most pro-inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
(151 reference statements)
1
17
0
4
Order By: Relevance
“…It happens as a result of the biological response of macrophages over the biomaterial. Macrophages are body cells which induce bone growth, and their response is scientifically proved as better in biomaterials with pores and consequent rough surface, such as those produced by the powder metallurgy route (Silva et al, 2014;Silva, 2001;Anderson et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It happens as a result of the biological response of macrophages over the biomaterial. Macrophages are body cells which induce bone growth, and their response is scientifically proved as better in biomaterials with pores and consequent rough surface, such as those produced by the powder metallurgy route (Silva et al, 2014;Silva, 2001;Anderson et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity of cobalt has been partly attributed to generated cobalt ions, which are likely to stimulate the generation of reactive oxygen species (ROS) in different cells . Moreover, Co‐containing nanoscale particles can be incorporated by immune cells, for example, macrophages, thereby inducing the release of pro‐inflammatory mediators (e.g., interleukins and TNFα) . Furthermore, it is suggested that the formation of free radicals plays a role in the process of periprosthetic fibrosis and loosening of hip arthroplasty .…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt–chromium–molybdenum (CoCrMo) alloy has been in use as a biomaterial for nearly 90 years due to its advanced ability to resist wear and corrosion when compared to other alloys, however, CoCrMo is susceptible to many types of corrosion typically associated with mechanically assisted crevice corrosion (MACC) where the environment may be chemically and/or mechanically aggressive . During MACC, electrode potentials at the CoCrMo surface can shift as far negative as −900 mV (vs. Ag/AgCl) from an unabraded open circuit potential (OCP) of about −250 mV (vs. Ag/AgCl) .…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness and morphology has also been documented to impact inflammatory cell activation responses. Anti‐inflammatory cytokine (IL‐10) production is favored on microrough CoCrMo surfaces whereas pro‐inflammatory cytokine (TNF‐α, IL‐6, and IP‐10) production is favored on smooth CoCrMo surfaces …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation